COMPETENCY AND VALUES OF LOCAL WISDOM OF HIGH SCHOOL PRINCIPALS - Yohanes Harsoyo; Catharina Wigati Retno Astuti; Caecilia Wahyu Estining Rahayu (Jurnal Cakrawala Pendidikan, 2019)
The competency of secondary school principals needs to be developed. The development of school principals' competencies needs to pay attention to cultural aspects that develop in the surrounding community. This research was aimed to describe the school principal’s competencies according to National Education Ministry Regulation No. 13 (2007) about School Principal’s standard competencies and their competencies development based on the values of local wisdom. This piece of research was conducted quantitatively and qualitatively. The research samples were 30 school principals whom their schools were located in the regional of Mataraman cultures. Data was gathered by collecting questionnaires (open and closed questions) and also interviews. The data was analyzed quantitatively and qualitatively. The results of this study are as follows: first, the school principals have been good at social and personality competences, yet the managerial, entrepreneurial, and supervision competences were still in adequate level; second, school principals already comprehended the values of Sistem Among and some of them had been implemented them. However, they had not been comprehend the leadership values based on Asta Brata and Sastra Gending; third, most of leadership values were based on Asta Brata, Sistem Among, and Sastra Gending that were compatible to the school principals and used for developing their leadership.